Design, synthesis and SAR study of bridged tricyclic pyrimidinone carboxamides as HIV-1 integrase inhibitors. Issue 13 (1st July 2020) - Patel, Manoj; Naidu, B. Narasimhulu; Dicker, Ira; Higley, Helen; Lin, Zeyu; Terry, Brian; Protack, Tricia; Krystal, Mark; Jenkins, Susan; Parker, Dawn; Panja, Chiradeep; Rampulla, Richard; et al.
Graphical abstract: The design, synthesis and structure-activity relationships associated with a series of bridged tricyclic pyrimidinone carboxamides as potent inhibitors of HIV-1 integrase strand transferase are described. Structural modifications to these molecules were made in order to examine the effect on potency towards wild-type and clinically-relevant resistant viruses. Abstract: The design, synthesis and structure-activity relationships associated with a series of bridged tricyclic pyrimidinone carboxamides as potent inhibitors of HIV-1 integrase strand transfer are described. Structural modifications to these molecules were made in order to examine the effect on potency towards wild-type and clinically-relevant resistant viruses. The [3.2.2]-bridged tricyclic system was identified as an advantageous chemotype, with representatives exhibiting excellent antiviral activity against both wild-type viruses and the G140S/Q148H resistant virus that arises in response to therapy with raltegravir and elvitegravir.